Antiparasitic effect of biogenic iron nanoparticles against the fish ectoparasite Argulus siamensis: In vitro study: Antiparasitic effect of iron nanoparticles against Argulus - Brahmchari, R. K.; Kumari, Pushpa; Kumar, Saurav; Sharma, Rupam; K. Pani Prasad; Srivastava, P. P.; Raman, R. P. (Indian Journal of Fisheries, 2023)
Argulus, an ectoparasite of fish which is ubiquitous in wild and culture ponds, poses a major challenge with severe economic losses to the global aquaculture industry. With the increase in intensification of aquaculture practices, there is a dire need to discover new therapeutic options in the treatment of argulosis owing to the limited effectiveness of existing drugs and chemicals and their significant side effects. The use of metal nanoparticles has shown promising results in the management of several parasitic infections. In this prelude, antiparasitic effect of biosynthesised iron nanoparticles was evaluated against Argulus siamensis under in vitro condition. Iron nanoparticles (FeNPs) were biosynthesised using fresh Bauhinia racemosa leaf extract as a reducing agent and were characterised using UV-VIS spectrophotometry, dynamic light scattering (DLS) technique, zeta potential measurements, transmission electron microscopy (TEM), scanning electron microscopy (SEM), and fourier transform-infrared spectroscopy (FT-IR). For estimating antiparasitic efficacy of FeNPs under in vitro test, ten adult and juvenile parasites each were challenged for 6 h separately in 20 ml of five different concentrations of FeNPs test solutions viz. 1.00, 1.25, 1.50, 1.75 and 2.00 mg ml-1 in triplicate along with control groups for adults whereas, for juveniles, it was 0.75, 1.00, 1.25, 1.50 and 1.75 mg ml-1. Formation of FeNPs was measured in 370-400 nm UV range. DLS showed an average FeNPs particle size of 119.8 nm with a polydispersity index of 0.311. Zeta potential measurements showed negative surface charges (-11.3 mV) whereas, SEM and TEM micrographs revealed synthesised nanoparticles were nearly spherical and size ranged from 60-270 nm. Further, FT-IR spectrum showed the presence of Fe-O, N=O and O-H groups. Argulocidal effectiveness in both cases was found to be concentration-dependent. The highest argulocidal activity of FeNPs was observed at concentration of 1.75 mg ml-1 for juveniles and 2.00 mg ml-1 for adult argulids which led to 100 and 87% mortality, respectively, in 6 h, however no mortality was recorded in control group up to 16 h. Furthermore, the calculated 6 h-EC50 of biosynthesised FeNPs for juvenile and adult argulid parasites was determined as 0.97 and 1.27 mg ml-1. Results of the present study showed that short term bath treatment with biosynthesised FeNPs is effective against argulid parasites. However, further research is required to evaluate its therapeutic potential under in vivo condition. Keywords: Argulosis, Argulus siamensis, Iron nanoparticles, Parasiticidal activity